PENGARUH PENERAPAN E-FILLING DAN KESADARAN WAJIB PAJAK TERHADAP KEPATUHAN PELAPORAN SPT TAHUNAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus pada KPP Pratama Surakarta) - Berliana Ridhani Putri, Fadjar Harimurti & Suharno (Universitas Slamet Riyadi, 2017)
The purpose of this research are to know the influence e-filling implementationand taxpayers awareness toward the annual notice of personal taxpayers complianceat KPP Pratama Surakarta. This research is a surveying study in the taxpayerswhich have registered at KPP Pratama Surakarta. All of taxpayers who use e-fillingat KPP Pratama Surakarta become population of this research with 100 samples.The data use quantitative and qualitative, the data also colected by questinonnairesand literatures. Research instrument test to analize data use classical assumptiontest, multiple regression, T- F test, and coeffisien determination test (R2). TheAnalysis result obtained determination coefficient R2 = 0,516, it means the influencevariable of e-filling implementation and taxpayers awareness toward the annualnotice of personal taxpayers compliance is 51.6%. F Test Result shows positiveinfluence and significance simultaneously toward annual notice of personaltaxpayers compliance. E-filling implementation and taxpayers compliance havepositive influence and significance toward annual notice of personal taxpayerscompliance. The awareness taxpayers have positive influence and significancetoward annual notice of personal taxpayers compliance.Keywords: e-filling implementation, taxpayers compliance, annual notice of personaltaxpayers compliance